Peri-operative silent myocardial ischaemia and long-term adverse outcomes in non-cardiac surgical patients. - Higham, H; Sear, J; Neill, F; Sear, Y; Foëx, P (2001)
Two hundred and seventy-five non-cardiac surgical patients were recruited to determine risk factors associated with the development of postoperative cardiovascular complications during the first year after surgery. Patients underwent ambulatory electrocardiography pre- and postoperatively. There were 34 adverse events over the whole study period. Twenty-four occurred within 6 months and the remaining 10 occurred between 6 and 12 months postoperatively. Silent myocardial ischaemia was associated with adverse outcome over both the first 6 months [OR 4.44 (95% CI 1.77-11.13)] and the whole study period [OR 2.81 (1.26-6.07)]. Other risk factors were: vascular surgery [OR 17.09 (2.67-351.44)], history of angina [OR 6.29 (2.21-17.62)], concurrent treatment with calcium entry blockers [OR 2.68 (1.03-6.93)] and smoking [OR 4.93 (2.00-12.02)]. None of these was a useful predictor of long-term outcome (between 6 and 12 months postsurgery). These results are at variance with other published data, but we conclude that monitoring for peri-operative silent myocardial ischaemia does not aid the prediction of long-term cardiovascular complications.